A comprehensive assessment of heavy metal contamination in road dusts along a hectic national highway of Bangladesh: spatial distribution, sources of contamination, ecological and human health risks. (3rd July 2022) - Kabir, Md. Humayun; Kormoker, Tapos; Shammi, Rifat Shahid; Tusher, Tanmoy Roy; Islam, Md. Saiful; Khan, Rahat; Omor, Md. Zohir Uddin; Sarker, Md. Eusuf; Yeasmin, Marjana; Idris, Abubakr M.
Abstract: Human activities around or within national highways, combined with atmospheric mixing, produce road dust, which can cause health problems through a variety of exposure routes. Thus, the study was aimed to investigate the contamination, spatial distribution, potential ecological and human health risks of various toxic heavy metals such as lead (Pb), copper (Cu), chromium (Cr), cadmium (Cd), zinc (Zn), nickel (Ni) and arsenic (As) in road dusts samples collected from traffic load and land-use types along the hectic Kushtia-Jhenaidah national highway, Bangladesh. The mean concentrations of Pb, Cu, Cr, Cd, Zn, Ni and As were found as 50.8 ± 15.7, 82.6 ± 17.2, 20.1 ± 5.7, 0.18 ± 0.06, 126.2 ± 40.7, 14.1 ± 4.7 and 0.12 ± 0.04 mg/kg, respectively, whereas Pb, Cu, Cd and Zn were evidently several times higher than the respective background values. The values of variance of coefficient (VC) exhibited that magnitudes of metal pollutions across the study sites were dominated by anthropogenic activities, while the principal component analysis (PCA) and cluster analysis (CA) identified vehicular and industrial emissions as the major sources of heavy metals in road dusts. The geo-accumulation index ( I geo ) values indicated that most of the dust samples were unpolluted to moderately polluted by heavy metals. The contamination factor (CF) values were found in the following order: Cu > Pb > Zn > Cd > Ni > Cr > As, while the contamination degree (CD) values indicated moderate to considerable level of contamination. Furthermore, the study site posed low to moderate ecological risks, despite the fact that non-carcinogenic and carcinogenic threats from various pathways of exposure appear insignificant, with children being more vulnerable than adults.